Optimizing Cattle Farm Waste Management Through the Application of Biogas Technology in Kondoano Village, Mowila Subdistrict, South Konawe Regency - Has, Hamdan; Aka, Rahim; Rahadi, Syam; Fadilla, Zahra Jinan; Puspitarini, Oktavia Rahayu (Indonesian Journal of Community Services, 2025)
Cattle waste is one of the common problems in cattle farms. Through proper processing, waste can be turned into new products with higher added value. This community service program takes the form of technical guidance provided by the Faculty of Animal Husbandry Team at Halu Oleo University to farmers. This activity aims to improve farmers' knowledge and skills in processing ruminant manure waste so that it can become an alternative energy source through the use of biogas technology. This activity was carried out in Kondoano Village, Mowila District, South Konawe Regency. The method of implementation began with a site survey, analysis of the problems experienced, exploration of the potential in Kondoano Village, technical guidance, and evaluation of the activities. Kondoano farmers were given additional knowledge through technical guidance on the application of biogas technology by utilizing livestock waste to produce energy and reduce environmental pollution. This activity involved a team of lecturers from the UHO Faculty of Animal Husbandry, students, and farmers. This technical guidance has been able to provide additional knowledge for the community to independently process livestock waste into biogas.